EFEKTIVITAS NATURAL FACE MASK DALAM MENINGKATKAN KELEMBABAN KULIT WAJAH - Masluhiya AF, Swaidatul; Fidiastuti, Hasminar Rachman (Universitas Tribhuwana Tunggadewi, 2019)
This study aimed to determine the effect of using natural masks to moisturize dry skin. This natural mask was made of ingredients that are safe to use and based on special formulations which include; bengkoang powder (2 grams), chocolate powder (1 gram), black cumin oil (0.6 ml), and honey (5 ml). This formulation was made so that the resultied mask formed paste stucture that can be directly applied. Masks were given to ten probandal women who have dry skin types and are 30-40 years old. Masks were used twice / week for six weeks (12 times usage). The instrument used to measure the moisture level of facial skin was a skin analyzer (HL-611) by directly attaching it to the face area and the results can be seen after 4-5 seconds. The data were analysed using ANOVA test 95% confidence interval and significance test using SPSS 15 for windows. The results showed that skin moisture values increased around 3.9% within 6 weeks of use, with a 0.8% increase at week 2, at week 4 there was an increase of 1.65% and at week 6 there was an increase in skin moisture by 1.4%. The moisture value of the skin on the face area (forehead, nose, chin, cheeks) showed no significant difference with almost the same value of humidity. It is recommended for dry skin types to use a face mask that contains oil as a skin lubricant and to protect water evaporation from the skin. It is necessary to do further testing on this natural mask so that safety on the skin can be guaranteed. It needs to be done so that the final product obtained meets the face mask safety quality standards set by the government. Keywords: Bengkuang; cocoa; black cumin; honey; natural mask.